Women's financial planning for retirement: Systematic literature review and future research agenda. Issue 1 (4th February 2019) - Kumar, Satish; Tomar, Sweta; Verma, Deepak
Abstract : Purpose: The purpose of this paper is to examine the status of the research on women's financial planning for retirement. This paper provides a brief review of the work carried out so far along with a conceptual framework of factors influencing women's retirement financial planning. In addition, it lists significant gaps and recommends avenues for future research. Design/methodology/approach: The review is based on 151 articles appearing in various peer-reviewed journals published during 1980–2017. The study establishes its prominence by studying the publication activities based on the year of publication and region, citation analysis, research designs, data analysis techniques and findings from the selected articles. Findings: Most of the literature on women's financial planning for retirement indicates a lack of financial management amongst women and their susceptibility to poverty in postretirement years. The majority of the research works in this field have taken place in developed economies. Empirical research with regression-based models for analysis is the most popular research design. This review also highlights the significant determinants of women's retirement financial planning as identified through literature. These include socio-demographic factors, psychological constructs, financial literacy, economic and circumstantial forces. Originality/value: This paper covers the research works done in this area in the past 38 years. To the best of authors' knowledge, this is the first attempt to provide a systematic and comprehensive compilation of the knowledge in this subject. It further synthesizes the findings of various studies on factors influencing women's retirement financial planning and gives recommendations for future studies.